Analisis wacana kritis dalam pembelajaran: Peran AWK pada pembelajaran literasi kritis, berpikir kritis, dan kesadaran berbahasa kritis - Sarasati, Ruruh (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2019)
Critical discourse analysis has been used to determine the power relations thatoccur in the process of production and reproduction of meaning. The structure ofknowledge influences the course of the practice of disclosure. The intendedknowledge is not only knowledge that is known by the speaker, but the knowledgeof the listener or reader. This places critical discourse analysis in a multidisciplinaryview. The multidisciplinary view is currently inherent in the analysis of criticaldiscourse and raises the potential for the involvement of critical discourse analysisin the discourses that arise in the classroom. Furthermore, critical discourse analysiscan also play a role in learning. This article conveys the potential role of CriticalDiscourse Analysis in critical literacy learning, critical thinking, and criticallanguage awareness.